Bioremediation of oil sludge contaminated soil by co-composting with sewage sludge - Chua, C.-L.; Isa, M.H. (2006)
This study determined the optimum ratio of contaminated soil to sewage sludge (organic amendments) in enhancing the biodegradation of refinery oil sludge. It also evaluated the treatment efficiency of refinery oil sludge by composting and the effect of sewage sludge addition on the biodegradation of refinery oil sludge. Experiments were conducted in six laboratory scale composting bins, each with 5 kg of soil. The composters were kept at 23 – 25 °C in a laboratory. The soil was spiked with petroleum refinery oil sludge (10 %, dry weight basis). All composters were supplemented with grass (bulking agent) at a soil-to-grass ratio of 1:0.5 (v/v). The ratios of contaminated soil to sewage sludge were 1:0 (control), 1:0.1, 1:0.3, 1:0.5, 1:0.7 and 1:1 (w/w). The contents of each composter were tilled and well mixed weekly after which samples were drawn for analysis. The experiment showed enhanced biodegradation of oil and grease due to sewage sludge addition. The maximum oil and grease removal achieved was 65.6 % over the 9 week study period under low temperature conditions, for the contaminated soil to sewage sludge ratio of 1:0.5. The remaining (34.4 %) was considered recalcitrant; stubbornly adsorbed onto soil particles and/or trapped in soil macro and micro pores and thus non-available to microorganisms.